Knowledge and attitude among Malaysian secondary school athletes on sports-related concussion - Fairus Fariza Zainudin (LPMPP Universitas Negeri Yogyakarta, 2022)
Adolescents' knowledge and attitude toward concussions are important in reducing the effects of post-concussion syndrome. To date, no standard education has been applied to Malaysian school-aged athletes. This study aims at identifying the level of knowledge and attitudes towards concussions among secondary school athletes. A cross-sectional survey with a purposive sampling method was employed. This study included 190 athletes at State Sports School. The RoCKAS-ST questionnaire was used to assess the knowledge and attitude of respondents on concussions. Independent t-tests were used to analyze differences in knowledge and attitudes score toward concussion between gender (male, female), sports type (contact, non-contact), and competition rank (U15, U18) with p 0.05. There was no significant difference, p 0.05 for both Concussion Knowledge Index (CKI) and Concussion Attitude Index (CAI) score between male and female athletes in contact and non-contact sports athletes. Age differences did not influence CKI scores. However, there was a significant difference, p 0.05 for the CAI score between the age categories of under-15 athletes (U15) and under-18 athletes (U18). In conclusion, age level influenced athletes' attitudes toward concussions. The younger athlete was more vulnerable to concussion injury. Therefore, developing a standard SRC education program for young Malaysian athletes is strongly recommended for concussion management.